2021
DOI: 10.3389/fimmu.2021.751337
|View full text |Cite
|
Sign up to set email alerts
|

Virus Infection Is an Instigator of Intestinal Dysbiosis Leading to Type 1 Diabetes

Abstract: In addition to genetic predisposition, environmental determinants contribute to a complex etiology leading to onset of type 1 diabetes (T1D). Multiple studies have established the gut as an important site for immune modulation that can directly impact development of autoreactive cell populations against pancreatic self-antigens. Significant efforts have been made to unravel how changes in the microbiome function as a contributor to autoimmune responses and can serve as a biomarker for diabetes development. Lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 190 publications
(235 reference statements)
0
11
0
Order By: Relevance
“…Independently, both enterovirus infection and dysbiosis have been frequently linked to T1D onset and are thus considered key environmental factors, but they have yet to be studied together and this precludes analyses of combined effects and cross-talk. Dysbiosis caused by infection can alter the microbiome in a prolonged or sustained way and these changes have downstream effects on the immune system, including heightened inflammation and reduced activation thresholds that can contribute to autoreactivity in humans (55). In this study, we show that CVB4 infection is capable of driving microbiome dysbiosis, disrupting intestinal physiology, promoting bacterial translocation, and altering host responses to commensal bacteria to ultimately promote the onset of autoimmune diabetes in NOD mice.…”
Section: Discussionmentioning
confidence: 63%
“…Independently, both enterovirus infection and dysbiosis have been frequently linked to T1D onset and are thus considered key environmental factors, but they have yet to be studied together and this precludes analyses of combined effects and cross-talk. Dysbiosis caused by infection can alter the microbiome in a prolonged or sustained way and these changes have downstream effects on the immune system, including heightened inflammation and reduced activation thresholds that can contribute to autoreactivity in humans (55). In this study, we show that CVB4 infection is capable of driving microbiome dysbiosis, disrupting intestinal physiology, promoting bacterial translocation, and altering host responses to commensal bacteria to ultimately promote the onset of autoimmune diabetes in NOD mice.…”
Section: Discussionmentioning
confidence: 63%
“…Schneider and von Herrath (2014) found that viral infections may act as a longitudinal factor during the induction of autoimmune antibodies against pancreatic β-cells and progression to DM type 1 (DM1). Similarly, other studies also report that infections accelerate the initiation and progression of autoantibodies synthesis at an early stage of the disease and lead to clinical DM1 (Dotta et al, 2007;Morse and Horwitz, 2021). Likewise, DM2 is also associated with infections, including Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Acinetobacter baumannii, SARS-CoV-2, HBV, HCV, HHV8, HSV1, and H1N1 virus (Gan, 2013;Leung and Liu, 2019;Lontchi-Yimagou et al, 2021;Carrillo-Larco et al, 2022).…”
Section: Introductionmentioning
confidence: 79%
“…Several enteric virus infections are also associated with DM pathogenesis. Viral infections are the instigator of gut dysbiosis and disruption of intestinal homeostasis that lead to subclinical enteropathy before DM1 onset ( Morse and Horwitz, 2021 ). Fabiani et al (2018) found that infection with the hepatitis C virus was associated with an elevated risk of DM2 and vice versa DM2 raised the risk of liver cirrhosis in HCV patients.…”
Section: Common Sites Of Infection and Prevalent Pathogensmentioning
confidence: 99%
“…This is important as it offers an explanation for the interaction between the intestinal flora, glycaemic control, and body mass index ( 32 ). Also, virus can influence the intestinal flora; there is a connection between enterovirus and dysbiosis of bacteria ( 33 ).…”
Section: The Intestinementioning
confidence: 99%